A Review of Internet Use and Access for BRICS Sustainable Futures: Opportunities, Benefits, and Challenges - Matli, Walter; Malatji, Masike (Journal of Information System and Informatics, 2024)
Access to the internet and modern technologies have acted as a catalyst for increasing digital literacy skills in society over the last few decades. The use of modern technologies within society has accelerated disproportionately. Digital literacy and access to modern technology products have been described as beneficial to addressing the knowledge and skills deficit. Yet, insights concerning the comparisons of BRICS member countries in addressing literacy/digital skills and sustainable and affordable access to modern technology products, as well as internet delivery, remains nascent. The current literature lacks comparative studies on internet use and access. This study uses Technology Acceptance Model (TAM) constructs to better understand internet use and access among some of the BRICS member states. The purpose of this qualitative study is to carry out a review that compares internet use and access among the five member states. It is key to understanding trends in technology products, processes, people, and real-time data sharing among BRICS members. It draws on the available reports in English on internet access and use. Then, it analyses and provides a discussion on the relationships between different countries and possible opportunities. This study concludes that the affordability of internet access remains a challenge. The challenge is further exacerbated by the demand to have access before one is at liberty to effectively use it. On the other hand, the challenge for people with access to the internet is to understand and reap the full benefits of usage. These results are specifically discussed, with implications for research and practices within BRICS member states. Several limitations to the study are presented, which in turn opens up potential future research perspectives. In conclusion, BRICS members should continue forging strong links to navigate new opportunities and identified challenges.